2019
DOI: 10.1111/jpi.12545
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin prevents early pituitary dysfunction induced by sucrose‐rich diets

Abstract: While physiological levels of glucocorticoids are required to ensure proper functions of the body, consistently high levels may engender several deleterious consequences. We have previously shown an increase in the activity of the hypothalamic‐pituitary‐adrenal (HPA) axis in rats fed sucrose‐rich diets (SRD). The main goal of this study was to analyze the processes involved in the modulation of the pituitary production of ACTH by SRD, and to test melatonin as a possible therapeutic agent for the prevention of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 89 publications
0
7
0
3
Order By: Relevance
“…Melatonin has been reported to be an important regulator of NAFLD/NASH by previous studies . Moreover, melatonin modulates NAFLD‐associated disorders such as insulin resistance, obesity, diabetes, and endothelial dysfunction . However, the exact mechanism of melatonin in NAFLD is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin has been reported to be an important regulator of NAFLD/NASH by previous studies . Moreover, melatonin modulates NAFLD‐associated disorders such as insulin resistance, obesity, diabetes, and endothelial dysfunction . However, the exact mechanism of melatonin in NAFLD is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…This is plausible according to a recent study, which found that the first cycle of breast cancer chemotherapy disrupted the sleep-wake activity rhythm and it decreased sleep efficiency and melatonin secretion [22]. The majority of information available about melatonin protective effects involve an interaction with several neurotransmitter systems, including the GABAergic, serotoninergic [63], glutamatergic and nitrergic [64], as well as the modulation of the hypothalamic-pituitary-adrenal axis [65]. As aforementioned, its effect also involve the neuroplasticity mechanism, which can explain the concurrent changes in neuroplasticity markers and the improvement of depressive symptoms and sleep quality in the current study.…”
Section: Plos Onementioning
confidence: 96%
“…Nuestra hipótesis sobre la participación de procesos oxidativos/inflamatorios en el desarrollo de la disfunción pituitaria parece ser consistente con la prevención inducida por la melatonina del aumento de los niveles hipofisarios y sistémicos de ACTH y corticosterona en ratas tratadas con DRS 66 . En ese sentido, estudios previos demostraron que la administración de melatonina (durante cinco días) redujo significativamente la secreción de corticosterona, atenuó la respuesta adrenocortical al estrés y aumentó la sensibilidad del eje HHA a la supresión por glucocorticoides 67,68 .…”
Section: Resultsunclassified
“…Los DAMPs generados como consecuencia de los efectos nocivos del estrés oxidativo/nitrosativo sobre componentes celulares, atraen y estimulan macrófagos para producir citoquinas, que a su vez impactan en la producción de POMC por los corticotropos. Evidencias en favor de este mecanismo se obtuvieron recientemente en nuestro laboratorio 66 . No puede descartarse que la melatonina también bloquee la inhibición por ROS del efecto de los glucocorticoides sobre la producción de POMC, según lo descrito por Asaba et al 75 .…”
Section: Resultsunclassified